Postoperative psychiatric disorders in general thoracic surgery: incidence, risk factors and outcomes - Ozyurtkan, Mehmet Oguzhan; Yildizeli, Bedrettin; Kuscu, Kemal; Bekiroglu, Nural; Bostanci, Korkut; Batirel, Hasan Fevzi; Yuksel, Mustafa (Oxford Univ Press Inc, 2010)
Objective: Postoperative psychiatric disorders (PPDs) may complicate the post-surgical outcome. We analysed the types, incidences, risk factors and outcomes of the PPDs in non-cardiac thoracic surgery patients. Methods: All patients (n = 100) undergoing major non-cardiac thoracic surgery from January 2004 to March 2005 were investigated prospectively. The diagnosis of PPD was made based on the Diagnosis and Statistical Manual of Mental Disorders. The patients were grouped into two according to the presence (group I) or absence (group II) of PPD. Data on pre-, per- and postoperative factors, and the adverse outcomes were analysed. Results: Eighteen patients (18%) developed PPD, including delirium in 44%, adjustment disorders in 22%, panic attack in 17%, minor depression in 11% and psychosis in 6%. The patients who developed PPD were older (58 +/- 17 vs 50 +/- 15 years, p = 0.05), had a longer operation time (6 +/- 1 vs 5 +/- 2 h, p = 0.015) and hospital stay (13 +/- 9 vs 8 +/- 5 days, p = 0.019). The morbidity and mortality rates were not significantly different between the groups (67% vs 46%; 11% vs 1%, respectively). The causative factors in the development of PPD were older age, longer operation time, abnormal serum chemistry values of sodium, potassium, calcium and glucose, hypoalbuminaemia, the presence of the postoperative respiratory distress and infection and blood transfusion (p < 0.05). Conclusions: PPDs are associated with adverse outcomes including a longer hospital stay, and increased morbidity and mortality rates. The identification, detection and elimination of these risk factors are recommended. (C) 2009 European Association for Cardio-Thoracic Surgery. Published by Elsevier B.V. All rights reserved.
Keywords: Biochemistry; Outcomes; Postoperative care; Surgery; Complications